Pastoral Accompaniment for Congregants Experiencing Fear of Divine Punishment - Donny Charles Chandra; Mie Lia; Yogi Mahendra (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Fear of divine punishment is a spiritually charged form of distress that appears in ordinary religious struggle, moral injury, shame-based faith formation, and, in some cases, scrupulosity. This article examines pastoral accompaniment for Christian congregants who interpret suffering, intrusive thoughts, moral imperfection, or ordinary uncertainty as evidence that God is angry and punitive. The study addresses a constructive problem: many pastoral responses either normalize fear as evidence of seriousness before God or dismiss it as irrational anxiety, yet both responses can intensify spiritual distress. Using a conceptual qualitative design, the article synthesizes peer-reviewed studies on religious and spiritual struggles, scrupulosity, spiritually integrated care, moral injury, and practical theology. The analysis proposes that pastoral care should neither dilute theological seriousness nor reinforce punitive images of God. Its main synthesis is a threefold pastoral framework, differentiated assessment, grace-oriented theological reframing, and collaborative accompaniment that includes referral when symptoms suggest obsessive-compulsive disorder, trauma, depression, or suicidal risk. The article concludes that effective pastoral accompaniment moves congregants from retributive anxiety toward secure attachment to God, morally responsible agency, and communal practices of confession, assurance, lament, and restoration. The contribution is a constructive model for churches that treats fear of divine punishment as a theological-psychological struggle requiring discernment, doctrinal care, ethical boundaries, and interdisciplinary cooperation.